DEVELOPMENT OF INDONESIAN LANGUAGE TEACHING MATERIALS FOR FOREIGN SPEAKERS (BIPA) BASED ON THE CULTURE OF BANGKA BELITUNG IN THE ENGLISH EDUCATION STUDY PROGRAM AT IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG - Ihda Husnayaini; Indrawati (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study This study aims to develop Indonesian for Foreign Speakers (BIPA) teaching materials based on Bangka Belitung culture to prepare students of English Language Education (TBI) at IAIN Syaikh Abdurrahman Siddik Bangka Belitung as prospective BIPA teachers. The research employs a qualitative descriptive design with a research and development orientation. Data were collected through a needs analysis using questionnaires and interviews with fourth-semester TBI students and lecturers, as well as document analysis of existing BIPA syllabi and teaching materials. The needs analysis examined students’ language skills, language components, learning motivation, teaching styles, classroom management abilities, and familiarity with instructional strategies. Based on the findings, culture-based BIPA teaching materials were designed by integrating Bangka Belitung cultural content into listening, speaking, reading, and writing activities. Local cultural elements, including traditions, social practices, and regional values, were embedded to enhance communicative competence and intercultural awareness. To ensure the quality of the developed materials, content validity, design validity, and construct validity were applied through expert judgment and revision processes. The results indicate that the Bangka Belitung culture-based BIPA teaching materials are pedagogically appropriate, culturally relevant, and feasible for classroom implementation. This study concludes that integrating local culture into BIPA teaching materials not only supports effective Indonesian language learning for foreign speakers but also contributes to the internationalization of the Indonesian language and the preservation of regional cultural identity